Pengaruh Work-Life Balance Dan Motivasi Kerja Pada Kinerja Karyawan Di PT Pelindo Marine Service - Niswah Brilliantia; Ika Korika Swasti (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The company possesses invaluable assets in the form of highly skilled human resources. Issues related to human resources can lead to a decline in employee performance, hindering the achievement of company targets. Several factors can influence employee performance, such as work-life balance and work motivation. This study aims to investigate the impact of work-life balance and work motivation on employee performance at PT Pelindo Marine Service, with a sample size of 56 individuals who have been working for more than 1 year, selected through probability sampling. In this study, respondents' opinions were measured using a Likert scale ranging from 1 to 5, based on statements provided in an online questionnaire. The data used were primary data obtained from employees and analyzed using SmartPLS 4 software. The research findings indicate that work motivation has a positive influence on employee performance. The variable of work-life balance also has a positive influence on employee performance. Higher work-life balance leads to better employee performance. When employees' work motivation increases, their performance also improves. Keywords: employee performance, job motivation, work-life balance